In-vivo biological activity and glycosylation analysis of a biosimilar recombinant human follicle-stimulating hormone product (Bemfola) compared with its reference medicinal product (GONAL-f). - Renato Mastrangeli; Abhijeet Satwekar; Francesca Cutillo; Cinzia Ciampolillo; Wolf Palinsky; Salvatore Longobardi (PLoS ONE)
Recombinant human follicle-stimulating hormone (r-hFSH) is widely used in fertility treatment. Although biosimilar versions of r-hFSH (follitropin alfa) are currently on the market, given their structural complexity and manufacturing process, it is important to thoroughly evaluate them in comparison with the reference product. This evaluation should focus on how they differ (e.g., active component molecular characteristics, impurities and potency), as this could be associated with clinical outcome. This study compared the site-specific glycosylation profile and batch-to-batch variability of the in-vivo bioactivity of Bemfola, a biosimilar follitropin alfa, with its reference medicinal product GONAL-f. The focus of this analysis was the site-specific glycosylation at asparagine (Asn) 52 of the α-subunit of FSH, owing to the pivotal role of Asn52 glycosylation in FSH receptor (FSHR) activation/signalling. Overall, Bemfola had bulkier glycan structures and greater sialylation than GONAL-f. The nominal specific activity for both Bemfola and GONAL-f is 13,636 IU/mg. Taking into account both the determined potency and the nominal amount the average specific activity of Bemfola was 14,522 IU/mg (105.6% of the nominal value), which was greater than the average specific activity observed for GONAL-f (13,159 IU/mg; 97.3% of the nominal value; p = 0.0048), although this was within the range stated in the product label. A higher batch-to-batch variability was also observed for Bemfola versus GONAL-f (coefficient of variation: 8.3% vs 5.8%). A different glycan profile was observed at Asn52 in Bemfola compared with GONAL-f (a lower proportion of bi-antennary structures [~53% vs ~77%], and a higher proportion of tri-antennary [~41% vs ~23%] and tetra-antennary structures [~5% vs <1%]). These differences in the Asn52 glycan profile might potentially lead to differences in FSHR activation. This, together with the greater bioactivity and higher batch-to-batch variability of Bemfola, could partly explain the reported differences in clinical outcomes. The clinical relevance of the differences observed between GONAL-f and Bemfola should be further investigated.